Improving environmental sustainability in construction : supplier collaboration approach - Malin, Johanna (My University, 2021)
The construction industry has great environmental impacts and it accounts to 39% of all of the world’s carbon emissions. Of these, the operational emissions, such as the energy to heat and light buildings, account for 28%, whereas the remaining 11% is associated with construction processes and materials throughout the lifecycle of the building. These impacts with the identified increased competitive advantage are pushing the companies in the construction industry to find ways to improve their environmental sustainability. In the construction industry supplier relationships are an important part of the business since 60-80% of all of the construction project’s costs come from purchases. This research aims to provide the case company, as well as other similar companies in the industry, methods to improve their environmental sustainability. This subject is looked at with the focus on supplier collaboration since it holds an especially significant place in the construction industry. The study uses green supply chain management and sustainability collaboration as the background for the theoretical framework. The study was conducted by interviewing a case company and its six suppliers. These six suppliers were picked due to their pioneer status in environmental sustainability in the Finnish construction industry. The study found different ways a construction company can improve their environmental sustainability, and that collaboration is a key element in achieving environmental objectives. These ways are setting sustainability objectives for the company, applying sustainability as a company value or to seek competitive advantage, implementing certified systems, practicing supplier supervision, finding eco-friendly production solutions, investing in product development, implementing personnel training, practicing recycling, finding eco-friendly logistic solutions, collaborating with stakeholders, implementing projects that improve environmental sustainability but that are not directly linked to company’s processes.
Keywords: green supply chain management, construction industry, environmental sustainability, sustainability collaboration